Peacebuilding in Northern Ireland: Photo-elicitation and Visual Methodologies as Instruments for Examining Post-agreement Societies - CLARK, SERENA (Trinity College Dublin. School of Religion. Irish School of Ecumenics, 2020)
The academic interest in cultural expressions and practices and their relationship to peace studies and conflict transformation is growing. These topics are primarily understood as processes that either perpetuate cultures of conflict and violence or facilitate peace and reconciliation. However, the use of cultural expressions like public art to evaluate the current conditions of post-agreement environments from the perspective of the local population has not been examined. Research suggests that in conflicts like Northern Ireland, cultural expressions and practices are not merely superficial phenomena but are essential indicators of how groups understand their lived experiences, replicating the environment in which they exist. As such, it is essential to explore these phenomena to understand the current state of post-agreement areas like Northern Ireland. Though there are many approaches for accessing post-agreement situations, this study explores the topic using a new approach that draws on the visual methodologies of photo-elicitation, iconography, and semiotics alongside deductive thematic analysis.
APPROVED
Keywords: iconography; peacebuilding; photo elicitation; semiotics; art; Northern Ireland; Belfast; post conflict; post agreement; visual methodologies; conflict resolution; conflict transformation; murals